Studi Optimalisasi Fasilitas Parkir di Fakultas Kedokteran (FK) serta Fakultas matematika dan Ilmu Pengetahuan Alam (FMIPA) Universitas Lampung - Putra, Rolan Ardeka; Sulistyorini, Rahayu; Sebayang, Syukur (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
University of Lampung (Unila) is the only one state university in Lampung. There are severalparking areas scattered in each faculty which serves as the campus facilities. The purpose of thisstudy is to find solutions for handling the parking problems in faculty of medicine(FK) andFaculty Mathematics and Natural Sciences (FMIPA) Unila.This study consisted of two phases, which collects parking data, such as a vehicle license platenumber, time of entry and exit of vehicle, and then analyze it with some formula that is used as aparameter conclusion. Some of these parameters are accumulation of vehicle parking, parkingindex, duration of parking, parking capacity, as well as parking turnover rate (PTO).From the analysis conclude that motorcycle parking area at FK can accommodate vehicleparking. While in the existing car parking area can't accommodate parking of vehicles. Then inFMIPA motorcycle parking area can also accommodate parking of the vehicles, whereas theexisting car parking area can't accommodate the vehicles parking neatly. As a solution of theparking problem, we will make plans of car parking area at the FK that can accommodate parkingof car vehicles in both faculties.Keywords : FK, FMIPA, parking index, parking duration , parking capacity, PTO